Analisis Kejadian Paritas dengan Perdarahan Postpartum Pada Ibu Hamil Anemia di RSUD Al-Ihsan Tahun 2021-2022 - Fayza Amelina Fitriyani; Jusuf Sulaeman Effendi; Sadeli Masria (Jurnal Riset Kedokteran, 2024)
Abstract. Based on the 2020 Indonesian Health Profile, maternal deaths are generally caused by bleeding, namely more than 1,330 cases. WHO states that 25% of the 100,000 maternal deaths overall are caused by postpartum hemorrhage every year. In West Java Province, around 2.54% of pregnant women experience birth canal bleeding. The level of parity in Indonesia is still relatively high. High parity is a risk factor for postpartum hemorrhage. The aim of this research is to determine the relationship between parity and postpartum hemorrhage in anemic pregnant women at Al-Ihsan Regional Hospital in 2021-2022. This type of research is analytical observational with a cross sectional approach. The population in this study was all birthing patients who experienced anemia at the Al-Ihsan Hospital in Bandung in 2021-2022, totaling 106 mothers who gave birth who experienced anemia and who did not experience anemia. The relsults of thel study baseld on unilvarilatel analysils showeld that 96 mothelrs who gavel bilrth elxpelrilelnceld anelmila, most of whom welrel ageld 25-35 yelars (66.7%), had thel parilty of 2 chilldreln (38.5%) and elxpelrilelnceld postpartum helmorrhagel (51%). Thel relsults of thel bilvarilatel analysils obtailneld a probabillilty valuel of 0.196 (p=0.196>0.05) that statilstilcally thelrel ils no silgnilfilcant rellatilonshilp beltweleln parilty and anelmila iln mothelrs who elxpelrilelncel postpartum helmorrhagel at Al-Ilhsan Relgilonal Hospiltal, Bandung. Thel conclusilon of thils study ils that thelrel ils no rellatilonshilp beltweleln parilty and postpartum helmorrhagel iln prelgnant womeln who elxpelrilelncel anelmila at Al-Ilhsan Relgilonal Hospiltal, Bandung. Abstrak. Belrdasarkan Profill Kelselhatan Ilndonelsila 2020, umumnya kelmatilan ilbu dilselbabkan karelna pelrdarahan, yaknil lelbilh daril 1.330 kasus. WHO melnyelbutkan bahwa 25% daril 100.000 kelmatilan ilbu selcara kelselluruhan dilakilbatkan olelh pelrdarahan postpartum seltilap tahun. Dil Provilnsil Jawa Barat ilbu hamill yang melngalamil pelndarahan jalan lahilr selkiltar 2,54%. Tilngkat pariltas dil willayah Ilndonelsila masilh telrbillang tilnggil. Pariltas tilnggil melrupakan faktor rilsilko telrjadilnya pelrdarahan postpartum. Tujuan pelnelliltilan ilnil melngeltahuil hubungan pariltas delngan pelrdarahan postpartum pada ilbu hamill anelmila dil RSUD Al-Ilhsan tahun 2021-2022. Jelnils pelnelliltilan ilnil adalah analiltilk obselrvasilonal delngan pelndelkatan cross selctilonal. Populasil pada pelnelliltilan ilnil adalah selluruh pasileln mellahilrkan yang melngalamil anelmila dil RSUD Al-Ilhsan Bandung Tahun 2021-2022, belrjumlah 106 ilbu belrsaliln yang melngalamil anelmila dan tildak anelmila. Hasill pelnelliltilan belrdasarkan analilsils unilvarilat dilkeltahuil daril 96 ilbu belrsaliln yang melngalamil anelmila, selbagilan belsar belrusila 25-35 tahun (66,7%), pariltas 2 anak (38,5%) dan melngalamil pelrdarahan postpartum (51%). Hasill analilsils bilvarilat dilpelrolelh nillail probabilliltas selbelsar 0,196 (p=0,196>0,05) bahwa selcara statilstilk tildak telrdapat hubungan yang belrmakna antara Pariltas delngan anelmila pada ilbu belrsaliln yang melngalamil Pelrdarahan Postpartum dil RSUD Al-Ilhsan Bandung. Kelsilmpulan daril pelnelliltilan ilnil adalah tildak telrdapat hubungan antara Pariltas delngan Pelrdarahan postpartum pada ilbu hamill yang melngalamil anelmila dil RSUD Al-Ilhsan Bandung.